Skin wound regeneration with bioactive glass-gold nanoparticles ointment. (8th February 2019) - Mârza, S M; Magyari, K; Bogdan, S; Moldovan, M; Peştean, C; Nagy, A; Tăbăran, F; Licarete, E; Suarasan, S; Dreanca, A; Baia, L; Papuc, I
Abstract: The bioactive glasses can lead to the promotion of growth of granulation tissue, while the gold nanoparticles (AuNPs) can induce the acceleration of wound healing including tissue regeneration, connective tissue formation, and angiogenesis. The aim of this study was to evaluate the impact of using the bioactive glass (BG) and BG-AuNPs composites on skin wound healing in experimental rat models for 14 days. Sol–gel derived BGs and BG-AuNPs composites mixed with Vaseline at 6, 12 and 18 wt% were used to evaluate the repair response of the skin. During the process of healing, granulomatous reaction was observed in the wound treated with 12 and 18 wt% BG-Vaseline ointments. Furthermore, a strong vascular proliferation and complete wound regeneration were found in 18%BG-AuNPs-Vaseline treated groups. The results derived from the performed investigations revealed that the 18% BG-AuNPs-Vaseline ointment is a promising candidate for wound healing applications.